PERAN PENDIDIKAN ISLAM DAPAT MENGATASI SIKAP AGRESI PECANDU NARKOBA DI SMA PABA BINJAI - Teuku Aulia; Hemawati Hemawati (UIN Sumatera Utara Medan, 2025)
This research aims to examine the role of Islamic education in overcoming aggressive attitudes in drug addicted students at SMA PABA Binjai. This research is motivated by the high rate of drug abuse among teenagers which causes the emergence of aggressive behavior, both in the school environment and in the community. Islamic education, with its values of self-control, patience and repentance, is believed to play an important role in helping overcome these problems. This research uses a qualitative approach with descriptive methods, using interview, observation and documentation data collection techniques. The research subjects consisted of drug addicted students, Islamic Religious Education (PAI) teachers, Guidance Counseling (BK) teachers, school principals, and students' parents. The results of the research show that Islamic education has a positive impact on reducing students' aggressive attitudes, by implementing religious values in everyday life, both at school and at home. Religion-based programs, such as learning congregational prayers, religious studies, and Islamic-based counseling, are effective in reducing the aggressiveness of drug addicted students. Even though there are challenges in implementation, such as limited resources and time, Islamic education at SMA PABA Binjai is proven to have a significant role in helping students overcome drug problems and aggressive behavior. This research suggests the need to strengthen religious-based character education programs and parental support in the student rehabilitation process.